WATER PRICING TO ACHIEVE SUSTAINABLE VALUE IN THE USE OF WATER FOR IRRIGATION IN NORTH COASTAL PLAIN, BALI - Budiasa, I Wayan (Bumi Lestari Journal of Environment, 2009)
TMB-59 is one of 39 irrigation systems under the project of Sustainable Development of Irrigated Agriculture in Buleleng and Karangasem Regencies, Bali (SDIABKA). This system, whose cost is amounting up to Rp 850,848,998.00, has been jointly financed by the European Commission and the Government of Indonesia. The average of groundwater discharged at TMB-59 was 12.93 l/s and the maximum discharge that was recommended by the project was 14.4 l/s. In case of water availability was limited, it was necessary that the discharge should be less than the recharge and the opportunity cost of water as well as depletion premium should be considered in designing tariff structure of water. Present water pricing by Tubewell User Group (TUG) of Sarining Pertiwi at TMB-59 considered operation and maintenance (OM) only – the costs in amounting to Rp 301.01/CM. The concept of sustainable value in the use of water fused the full supply cost, opportunity cost and externality cost. It was obtained that sustainable value in the use of water for irrigation in TMB-59 was Rp 1,218.29/CM consisting to full supply cost of Rp 631.26/CM, opportunity cost of Rp 188.74/CM, and depletion premium of Rp 398.29/CM. This amount, which was four times of OM costs or two times of full supply cost, and should be paid by users in order that irrigated agricultural development is to become sustainable.
Keywords: water; irrigation; cost; depletion; sustainability; Buleleng; Karangasem